78.5k views
2 votes
Factor completely: 2x2 - 6x - 56

(2x - 14)(x + 4)
(x - 7)(2x + 8)
2(x - 7)(x + 4)
2(x - 4)(x + 7)

User Barryrowe
by
5.8k points

2 Answers

4 votes
The correct answer is, C. 2(x-7) (x+4)

I hope this helps. :)

And have a great day. :D
User Shome
by
6.3k points
2 votes

Answer:

2(x - 7)(x + 4)

Explanation:

Given expression is,


2x^2 - 6x - 56

By the middle term splitting,


=2x^2-(14-8)x-56


=2x^2-14x+8x-56


=2x(x-7)+8(x-7)


=(2x+8)(x-7)


=2(x-7)(x+4)

Since, further simplification is not possible,

Hence, third option is correct.

User Perseverance
by
6.4k points